Effectiveness of Zilgrei Method Towards Labor Output Among Primigravida Mother in Indonesia - Nurwita, Ati; Sumarni, Rani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims : the study aimed to test the effectiveness of the zilgrei methode in primigravida mother with second stage labor of long second stage, incidence laceration, infant condition and the scale pain of labor. Methods : The study used a queasy experimental design with a control group, collecting primary data through observation, partographs, APGAR score, and pain scale assessment for 6 months. Result : The result of the bivariate test shows that the mean comparison of the long second stage was different between the two groups (p-value 0,001). No significant difference in the proportion of the incidence laceration (p= 0.370), APGAR score at first, fifth, and ten minutes (p>0.005). There was a significant comparison of pain scale between a group with and without Zilgrei Method (p=0.000). Conclusions : Based on the results of this study Zilgrei method can be applied as an alternative non-pharmacological method to shorten the second stage and reduce pain on labor. For further research, it is necessary to consider controlling the weight of a born baby and maternal risk factors to determine the effect of applying the Zilgrei method optimally to the laceration of the birth canal and the condition of the baby at birth.